2002
DOI: 10.1086/339857
|View full text |Cite
|
Sign up to set email alerts
|

ISOCAM Observations of Galactic Globular Clusters: Mass Loss along the Red Giant Branch

Abstract: Deep images in the 10 lm spectral region have been obtained for five massive Galactic globular clusters, NGC 104 (=47 Tuc), NGC 362, NGC 5139 (=! Cen), NGC 6388, NGC 7078 (=M15), and NGC 6715 (=M54) in the Sagittarius Dwarf Spheroidal using the ISOCAM on board the Infrared Space Observatory in 1997. A significant sample of bright giants have an ISOCAM counterpart, but only fewer than 20% of these have a strong mid-IR excess indicative of dusty circumstellar envelopes. From a combined physical and statistical a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 56 publications
3
96
0
Order By: Relevance
“…2 shows that the FIR spectral energy distribution (SED) of NGC 7078 is clearly inconsistent with the Rayleigh-Jeans tail of emission by its stellar content, the measured FIR emission exceeding the extrapolated stellar continuum by some three orders of magnitude. We also note that the magnitude and wavelength at which the excess is seen means that it is very unlikely to be due to the contribution of circumstellar dust (Origlia et al 2002). The only plausible explanation for the excess is emission by intra-cluster dust in the GC core.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…2 shows that the FIR spectral energy distribution (SED) of NGC 7078 is clearly inconsistent with the Rayleigh-Jeans tail of emission by its stellar content, the measured FIR emission exceeding the extrapolated stellar continuum by some three orders of magnitude. We also note that the magnitude and wavelength at which the excess is seen means that it is very unlikely to be due to the contribution of circumstellar dust (Origlia et al 2002). The only plausible explanation for the excess is emission by intra-cluster dust in the GC core.…”
Section: Resultsmentioning
confidence: 80%
“…Penny et al (1997) and Hopwood et al (1998) upper limits only, but Hopwood et al reported a marginal detection at 850 µm in the core of the metal-rich GC NGC 6356. Origlia et al (2002) carried out a deep survey of several GCs with ISOCAM. They concluded that prolific mass-loss occurs primarily near the tip of the red giant branch, is episodic, and does not seem to depend strongly on the GC metallicity.…”
Section: Introductionmentioning
confidence: 99%
“…The NGC 362, NGC 6388, and M 15 clusters were previously observed with ISOCAM by Origlia et al (2002).…”
Section: Mass-losing Stars: Previous Identificationsmentioning
confidence: 76%
“…Because T eff is derived spectroscopically, the gravity is recomputed through the Stefan-Boltzmann equation in each iteration according to the new value of T eff . The mass value of 0.82 M ⊙ is appropriate for RGB stars but probably too high for AGB stars, because of mass loss phenomena during the RGB phase (Rood 1973;Origlia et al 2002Origlia et al , 2007Origlia et al , 2014. In 6 Note that Simmerer et al (2013) adopted as solar reference value 7.56 obtained from their own solar analysis, while we used 7.50 by Grevesse & Sauval (1998).…”
Section: Analysis With Photometric Gravitiesmentioning
confidence: 99%